ARAHAN PENGATURAN DAN PENGENDALIAN BANGUNAN DI KECAMATAN PINANG KOTA TANGERANG - Hendrojogi, Windriarti (Badan Pengkajian dan Penerapan Teknologi, 2008)
Kecamatan Pinang is located in Kota Tangerang. The region has an important role in the regional development, specially for Kota Tangerang and DKI Jakarta. Nowadays the physical development some part of Kecamatan Pinang is very poor and crowded. There are no building development guidelines that guiding the physical development of settlement, commercial actifitives and other infrastructure. These conditions certainly caused many visual as well as economical and social problems. Commercial activities is obstructed, and the environment become unsave and uncomfortable. Concernng those it is necessary to formulate thebuilding development guidelines which is comprised of Building Demarcation Line (GSB), Buliding Coverage Ratio (KDB), Floor Coverage Ratio (KLB), and Building Elevated (TB). It is hope that the building code would create safety, pleasant, productive, and sustainable spatial in Kecamatan Pinang.